Аналіз ефективності універсального контакт-центру CALL-O-CALL - Сабурова, С. О.; Радченко, Р. В.; Кадацька, О. І. (ХНУРЕ, 2023)
An analysis of the implementation of CRM (Customer Relationship Management) technology in Call-o-Call carried out, which will ensure a strategy for sustainable business processes, the core of which is the “customerorientation” approach of piece intelligence. Тhis Call-o-Call strategy is based on a variety of advanced management and information technologies, in addition to which the company collects information about its clients at all stages of their life cycle (for radiant, attenuated, loyal), knowledge that is drawn from it is knowledge that is vikorist, that is knowledge for the benefit of one’s own I will be in business to establish mutually beneficial relationships with them. The result of the implementation of the Call-o-Call strategy is increased competitiveness of the company and increased profits, as well as correctly generated products, based on a personal approach to each client, allow can to receive new clients. They also help to wipe out the elderly.
Keywords: контакт-центр; CALL-O-CALL